2019
DOI: 10.1007/s00259-019-04533-y
|View full text |Cite
|
Sign up to set email alerts
|

[18F]Florbetapir PET/MR imaging to assess demyelination in multiple sclerosis

Abstract: Purpose We evaluated myelin changes throughout the central nervous system in Multiple Sclerosis (MS) patients by using hybrid [ 18 F]florbetapir PET-MR imaging. Methods We included 18 relapsing-remitting MS patients and 12 healthy controls. Each subject performed a hybrid [ 18 F]florbetapir PET-MR and both a clinical and cognitive assessment. [ 18 F]florbetapir binding was measured as distribution volume ratio (DVR), through the Logan graphical reference method and the supervised cluster analysis to extract a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
(59 reference statements)
1
17
1
Order By: Relevance
“…Second, EDSS and myelin changes were correlated in the longitudinal 18 F-florbetapir PET study, suggesting that myelin recovery might contribute to the decrease in EDSS score. Previous [ 12 , 22 ] and our present studies showed that EDSS was not related to 11 C-PiB or 18 F-florbetapir DVR in T2 lesions at baseline. Therefore, longitudinal amyloid PET reflecting the balance between the loss and recovery of myelin in patients with MS could better assess the development of clinical disease status of MS and disease-modifying treatments.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…Second, EDSS and myelin changes were correlated in the longitudinal 18 F-florbetapir PET study, suggesting that myelin recovery might contribute to the decrease in EDSS score. Previous [ 12 , 22 ] and our present studies showed that EDSS was not related to 11 C-PiB or 18 F-florbetapir DVR in T2 lesions at baseline. Therefore, longitudinal amyloid PET reflecting the balance between the loss and recovery of myelin in patients with MS could better assess the development of clinical disease status of MS and disease-modifying treatments.…”
Section: Discussioncontrasting
confidence: 45%
“…[12] and Carotenuto A, et al. [22] have reported a decreased binding of amyloid tracer in the area 2 to 8 mm outside the edge of the T2 lesion, suggesting that the range of demyelinating lesions reflected by amyloid PET might be larger than that defined by T2WI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But using these drugs requires an expensive laborious synthesis with confirmation of radio purity at each stage. The short half-lives of the currently used radionuclides 11 C (20.4 min) and 18 F (109.8 min) may also limit the widespread use of these imaging agents [11,12].…”
Section: Introductionmentioning
confidence: 99%